ANALISIS KETERSEDIAAN DAN KEBUTUHAN AIR IRIGASI UNTUK TANAMAN PADI STUDI KASUS DAERAH IRIGASI CIBANON KABUPATEN BOGOR - Nugroho, Hafiedh Adi; Darmadi (JURNAL TEKNIK SIPIL-ARSITEKTUR, 2026)
Food self-sufficiency, especially rice, is one of the government's strategic programs in terms of meeting the food needs of all Indonesians. Therefore, in order to achieve food self-sufficiency and utilize the potential of existing water resources, research was conducted on the analysis of the availability and demand for irrigation water for rice crops. This research is expected to provide answers on the potential of water resources and irrigation water requirements using the planning criteria method (KP-01). The results of the water availability analysis were obtained using the F.J. Mock method with a determination of the 80% reliability level (Q80). The calculation results show that the reliable discharge follows the rainfall pattern, with the highest value of 26.86 m³/second in February I and the lowest of 9.78 m³/second in July II. The Q80 discharge represents the minimum discharge that can still be relied upon as the basis for evaluating irrigation water availability. Calculations of water requirements using the rice-rice-rice cropping pattern in three cropping seasons starting in November, March, and July using the KP-01 method showed that the highest water requirements occurred in January I and June I at 0.40 m³/second, and in September I at 0.65 m³/second. In certain periods, negative water requirement values were obtained, indicating that effective rainfall had sufficiently met the needs of the crops. This shows that the potential of water resources originating from rainfall around D.I Cibanon is sufficient for rice cultivation throughout the season. For the reliability of the irrigation network, optimal maintenance and management of the network is necessary.